Sự phân tỏa vật liệu phù sa Sông Hồng ở Vịnh Bắc Bộ - Bách, Nguyễn Văn; Hải, Nguyễn Tiến; Thành, Đinh Xuân; Nguyên, Nguyễn Đình (Vietnam Journal of Earth Sciences, 2000)
Allocation of Red River sediment